Proximal tubular transcription factors in AKI: recent advances - Piret, Sian E. (Nephron, 2020)
The proximal tubule (PT) is a major target in acute kidney injury (AKI), leading to profound changes in PT cell biology. Among the genes with early and robust changes in expression are many transcription factors (TFs), which themselves account for other transcriptomic changes. Potentially important TFs are being revealed in large sequencing datasets; however, to understand whether these TFs account for adaptive or maladaptive changes requires further mechanistic studies, which may reveal novel therapeutic targets. This minireview will highlight the identification and biology of three novel TFs in AKI: Sox9, Foxml and Foxo3.